2022
DOI: 10.1002/wer.10765
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, identification, and discharge of microplastics from effluent and sludge of the largest WWTP in Iran—South of Tehran

Abstract: Microplastic pollution is a serious threat to the biota and humans, and wastewater treatment plants act as a pathway for entering microplastics into the environment. This study discusses the identification and quantification of microplastics in the south of Tehran municipal WWTP. The sampling was repeated three times in a month, overall, nine times for water samples and once a month in total, three times for digested sludge samples by steel bucket with the WPO method. The microplastics from water and digested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated that environmental factors, such as temperature, biochemical oxygen demand (BOD), total suspended substance (TSS) and turbidity, had the greatest influence on microplastics abundance in the Brantas River (Buwono et al, 2021). Various pathways contribute to the transport of microplastics from land to rivers, including runoff, rainstorms, atmospheric deposition, and sewage discharge from wastewater treatment plants, all of which are susceptible to human activities (Hurley et al, 2018;Oveisy et al, 2022;Trainic et al, 2020). Moreover, anthropogenic factors such as land use, urbanization have been reported to correlate strongly with microplastics abundance (Dai et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that environmental factors, such as temperature, biochemical oxygen demand (BOD), total suspended substance (TSS) and turbidity, had the greatest influence on microplastics abundance in the Brantas River (Buwono et al, 2021). Various pathways contribute to the transport of microplastics from land to rivers, including runoff, rainstorms, atmospheric deposition, and sewage discharge from wastewater treatment plants, all of which are susceptible to human activities (Hurley et al, 2018;Oveisy et al, 2022;Trainic et al, 2020). Moreover, anthropogenic factors such as land use, urbanization have been reported to correlate strongly with microplastics abundance (Dai et al, 2022).…”
Section: Introductionmentioning
confidence: 99%